Industrial revolution 4.0 implementation: current practice and barriers in manufacturing firms of Malaysia - Tay, Shu Ing (2020)
The Industrial Revolution 4.0 is the stage in the knowledge development in which the lines between digital, physical, and biological spheres are being distinct. Industrial Revolution 4.0 is controlled by digital physical frameworks and artificial intelligence that make human-machine interface more universal. Industry 4.0 was introduced by German during 2011, which is a contemporary issue that concerns today’s industrial production as a whole and is meant to revolutionize it at many countries. In Malaysia, where is still presently depend heavily on low cost foreign labor for their production, especially in the sector of manufacturing. Malaysia has been rather slow-moving to embrace Industry 4.0 if compared with neighboring countries like Thailand or Vietnam which already have Industry 4.0 policy frameworks earlier than Malaysia. This research aims to identify the current practices and implementation of industries 4.0 in Malaysia; and to determine the barriers encountered by the manufacturing firms in Malaysia on implementation of Industry 4.0. The scope of study was focused on the manufacturing industries in Malaysia which have been implementing the Industry 4.0.This research was conducted using qualitative approach where the data were obtained from seven manufacturing companies that implementing Industry 4.0 by choosing multiple case study alternative. Semi-structured interview and purposive sampling were used to obtain the relevant data. In this research, it was found that the current practice of implementation Industry 4.0 in Malaysia still at the initial stages according to respondents. Most of the companies involved in the study were at the beginning level to kick start the implementation Industry 4.0 in their organization. In additional, the big barriers faced by respondents were the data managements and integration and the education. Besides that, there were a few new barriers discovered from this study namely culture, competitor, mind set and environment. In conclusion, this research reveals the current practices and barriers that contributed and faced by all the manufacturing firms that can assist the government in preparation draft of national policy Industry 4.0 in Malaysia.